Influence Principal’s Leadership Style on Discipline Level of Madrasah Ibtidaiyah Darul Fikri - Marini, Marini; Iman, Nurul; Syam, Aldo Redho (Journal of Islamic Education, 2023)
This study aims to determine whether or not there is a significant influence between the leadership style of the madrasah principal and the level of discipline of the MI Darul Fikri teacher. The subjects of this study were all teachers of MI Darul Fikri as many as 27 teachers, sampling using a total sample of 27 respondents. In measuring the research variables, the researcher first tested the instrument, namely the validity test and the reliability test. Meanwhile, in measuring the effect of the two variables using the correlation formula and simple linear regression using SPSS 17 to find out the results of the data that has been done. Based on data processing which states that there is a significant influence between the leadership style of the madrasa principal and the level of discipline of MI Darul Fikri teachers, namely 61.3% and 38.7% the level of teacher discipline is influenced by other aspects.